Negotiating the Ethical Conduct of Educational Research in an Institutional Review Board Space: Perspectives from a University in Ethiopia - Alemu, Ashenafi (International Journal of African Higher Education, 2019)
Some international researchers assume that there is a lack of ethical review of research in many countries of the Global South. However, numerous African countries have recently introduced local and national research ethics guidelines. This article unpacks how ethical reviews of research in education are negotiated in a higher education institution in Ethiopia. It employs a critical analytical lens to challenge some of the assumptions of Beaty’s (2010) Institutional Review Board (IRB) stakeholder model. The article begins with a discussion of the limitations inherent in the IRB model. Critical analyses of institutional documents and non-confidential, off-the-shelf IRB minutes are also conducted. The analysis shows that researchers within the medical and health sciences disciplines have well established organizational engagement when it comes to handling issues related to research ethics. However, the limited representation of the educational and social and behavioral science disciplines remains a challenge. Furthermore, ethical issues in conducting educational research are hardly addressed in the national guidelines for granting research ethics approval. This results in further marginalisation of the contributions of educational research to knowledge production. Certains chercheurs internationaux présument un manque de suivi éthique de la recherche dans plusieurs pays du Sud. Cependant, de nombreux pays d’Afrique ont récemment mis en place des recommandations au niveau local et national en ce qui concerne l’éthique de la recherche. Le présent article analyse comment le suivi éthique de la recherche en sciences de l’éducation est mené dans un établissement d’enseignement supérieur en Ethiopie. Adoptant un point de vue analytique critique, il remet en question certains présupposés du modèle de l’Institutional Review Board (IRB – comité d’éthique de la recherche) de Beaty (2010) basé sur la théorie des parties prenantes. L’article commence par considérer les limites du modèle de l’Institutional Review Board. Des analyses critiques sont également menées à partir de documents institutionnels et de comptes-rendus disponibles et non confidentiels de réunions de l’Institutional Review Board. Cette recherche démontre que les chercheurs en médecine et sciences de la santé ont des positions clairement établies et propres aux organismes auxquels ils appartiennent, qui leur permettent de faire face aux questions d’éthique de la recherche. Cependant, la sous-représentation des sciences de l’éducation, des sciences sociales et des sciences comportementales demeure problématique. De plus, les questions éthiques qui se posent dans la recherche en sciences de l’éducation sont à peine abordées dans les directives nationales qui permettent d’obtenir l’approbation du comité d’éthique de la recherche. Cela a pour conséquence d’éloigner un peu plus les contributions de la recherche en sciences de l’éducation de la production du savoir.